MANAJEMEN PENGELOLAAN LEMBAGA AMIL ZAKAT DENGAN PRINSIP GOOD GOVERNANCE - AGUS PERMANA; AHMAD BAEHAQI (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2018)
This study describes about the management of zakat based on good governance principles. The method of this study is using library research such as secondary data in the form of books, journal articles or other literature based on the topic being discussed. The results of this study show that good governance is required by LAZ to improve professional performance in order to meet the interests of stakeholders. The implementation of Good Governance Principles in the management of zakat is as follows: Transparency, it means that LAZ must apply the principle of information disclosure to stakeholders. Accountability, it means that LAZ must hold the principle of trust (accountable) in managing zakat funds. Responsibility, it means that LAZ is responsible for distributing zakat funds right up to mustahiq. Independency, it means that LAZ is managed independently and has no dependence on certain people or other institutions. Fairness, it means that LAZ should make every effort to be fair in distributing zakat funds for those who are entitled to it. Sharia Compliance, it means that the collection and distribution of zakat funds managed by LAZ must comply with the Islamic corridor.